Bacteriological Study of Type 2 Diabetes - Hussain, Zainab Maythim; Kadhum, Tabark Hamza; Kadhum, Tabarak Amer; Mahdi, Ola Salah; Abd _aoun, Madiha Abd AL_Hussein (American Journal of Biology and Natural Sciences, 2024)
The study aimed to isolate and identify the types of bacteria that cause polycarbonate for patients with type 2 diabetes. Patients samples were collected from Al-Hussein Teaching Hospital in Kerbala for the period From March to May 2021, our results were isolated and diagnosed 30 samples, positive bacteria 80% more than negative bacteria 20 %.Nine isolates were Staphylococcus aureus (30%) .It was the most dominant bacteria in the culture medium, and 4 (13.33%) isolates with Staphylococcus saprophyticus, Hemolytic streptococci, Streptococcus viridians, 2 (6.67%) isolates from Escherichia coli , Klebsiella species, 3 (10%) isolates from Enterococcus, 1 (3.33%) isolate Pseudomonas aeruginosa, Proteus spp. The biochemical study showed an increased increase in the concentration of total cholesterol (PS0.05) in my poly and diabetes groups, as weil as in low-density fatty proteins, where they showed an increase in diabetes inflammation group, Fatty proteins showed The incidence of urinary tract infection varies with gender and age, where the infection occurs in both sexes, the incidence of females is more than the incidence of males, as a study indicated. The infection in females is three times that of males in the "first ten years of the child's life." The reason for the increase in the incidence of UTI in females is the shortness of the urethra in addition to its proximity to the anus.